BETWEEN RIGHTS AND SILENCES: A HISTORICAL-CRITICAL ANALYSIS OF THE EARLY CHILDHOOD EDUCATION CURRICULUM IN TOCANTINS - Almeida, Caritas Gomes de Oliveira; Brito, Katia Cristina Custódio Ferreira (Seven Editora, 2025)
Considering that curricular documents are not neutral, but historical productions shaped by societal projects and ideological disputes, this article problematizes the Tocantins Curricular Document – Early Childhood Education and the documents that guide Early Childhood Education in the municipality of Palmas-TO, in light of Historical-Dialectical Materialism, Historical-Critical Pedagogy, and Cultural-Historical Theory. It aims to analyze the pedagogical and curricular conceptions present in these documents, identifying foundations, limits, and contradictions related to the social function of Early Childhood Education and the role of teacher mediation. To this end, qualitative documentary research is conducted, using as corpus the Tocantins Curricular Document – Early Childhood Education, approved in 2019, and municipal regulations that govern the curricular and pedagogical organization of Early Childhood Education in Palmas. In this way, it is observed that the analyzed documents, although they recognize the child as a subject rights and value play, interaction, and experiences, maintain alignment with the National Common Curricular Base, prioritizing lived experiences, children’s protagonism, and learning rights over systematic teaching, cultural transmission, and the teacher’s intentional mediation. This allows us to conclude that such curricular guidelines have structural limitations, as they remain silent on the concrete material conditions of childhoods in Tocantins, reinforce neo-schoolist concepts, and weaken the school’s social function as a space for the socialization of historically produced knowledge, indicating the need for a curriculum reorganization based on critical, historical-dialectical, and emancipatory perspectives for public Early Childhood Education, in the context of contemporary Brazilian educational policies. DOI: https://doi.org/10.56238/sevened2025.036-147